2010 International Conference on Education and Management Technology 2010
DOI: 10.1109/icemt.2010.5657657
|View full text |Cite
|
Sign up to set email alerts
|

Quality of work life and organizational commitment amongst academic staff: Empirical evidence from Malaysia

Abstract: The purpose of this paper is to determine the level and relationship between quality of work life with organizational commitment amongst academic staff in one of the leading public universities in Malaysia.A survey instrument was used to measure the perception of academic staff concerning their level of quality of work life and its relationship to organizational commitment. A total of 300 sets of questionnaire were distributed to academic staff in selected faculties and 170 useable questionnaires were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
4
10
0
Order By: Relevance
“…organizational commitment increases by improved opportunity skills develop and continue learning). This finding is consistent with the findings studies of Daud [39] and Miller [43]. Meaning that learning and nurturing skills are among the critical factors affecting staff's quality of working life.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…organizational commitment increases by improved opportunity skills develop and continue learning). This finding is consistent with the findings studies of Daud [39] and Miller [43]. Meaning that learning and nurturing skills are among the critical factors affecting staff's quality of working life.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the research showed that there is a significant relationship between job security and organizational commitment; in other words, higher job security may lead to increased organizational commitment. The results of this finding are consistent with studies of Daud [39], Normala [27] and Chesley [46]. In an organization, job security is considered as one of the issues that affect the organization's employees, therefore a part of the mental and intellectual energy of the organization is dedicated to this issue.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the signifi cantly longer time given to research by the academics from the research universities, the time devoted to teaching-related activities is still high. In the last 5 years, it has been widely held that the workload of academics in research universities has increased if not doubled (Normala Daud 2010 ). While being cautious of exaggerated claims, it is important to note that the increase in working hours in recent times has indeed further pushed up the average work time in research universities to quite a high level.…”
Section: Research-teaching Nexusmentioning
confidence: 99%
“…When the literature is examined, there are many studies that reveal that there is a significant relationship between the quality work of life and organizational commitment of administrators and employees in different fields of study such as health, finance, education and military, and that quality of work life strongly influences/predicts organizational commitment (Aharon, Madjar, & Kagan, 2019;Ahmadian, Vafaeian, & Farshbaf, 2015;Akar, 2018a;Altay & Turunc, 2018;Barzoki & Sarand, 2015;Daud, 2010aDaud, , 2010bDaud, 2012;Daud, Yaakob, & Ghazali, 2015;Demir, 2016;Erdem, 2010;Farid, Izadi, Ismail, & Alipour, 2015;Heidarie, Askary, Saedi, & Gorjian, 2012;Hong, Tan, & Bujang, 2010;Sevgin, 2019;Saleem, 2017;Taşdemir Afşar, 2014;Yalcin & Akan, 2016). However, it is seen that the studies comparing the effect of quality of work life on administrators' and teachers' commitment to school/organization are limited.…”
Section: Introductionmentioning
confidence: 99%